2015
DOI: 10.1038/ejcn.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and sodium intake from snacks in adolescents

Abstract: Background/objectives: The relationship between sodium intake and arterial blood pressure (BP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
13
2
Order By: Relevance
“…In Australia, a study extracting dietary patterns of adolescents showed that participants with high scores of a Western dietary pattern, including sweet and salty snacks, were significantly associated with a greater risk of MetS (14). In our study, in particular salty snack consumption was positively associated with hypertension, even after controlling for BMI, results supported by observational and interventional studies showing that higher intakes of salt increase hypertension (13,15).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In Australia, a study extracting dietary patterns of adolescents showed that participants with high scores of a Western dietary pattern, including sweet and salty snacks, were significantly associated with a greater risk of MetS (14). In our study, in particular salty snack consumption was positively associated with hypertension, even after controlling for BMI, results supported by observational and interventional studies showing that higher intakes of salt increase hypertension (13,15).…”
Section: Discussionsupporting
confidence: 78%
“…A positive association between blood pressure and the frequency of consumption of salty snack foods was found with 50% of daily salt intake from salty snacks (13). Middle-school Italian adolescents also showed higher prevalence of overweight and obesity with higher frequencies and calorie intakes of daily snacks (7), findings in contrast to those among Greek adolescents with an average consumption of 90 g/d snacks, showing no significant association with MetS (8).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Summary. Ponzo and colleagues 23 examined the association between BP and overall sodium intake and sodium from processed snacks in a cross‐sectional study of 1200 Italian adolescents (aged 11–13 years) who were randomly selected from 6876 children participating in a school‐based health examination . All patients completed a 19‐item food frequency questionnaire (FFQ) that assessed snack consumption.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is no other study in children considering the relationship between BP and EDSF CF. One Italian study found high sodium snacks to be positively associated with SBP and DBP in adolescents [36]. However, Julián-Almarcegui et al, showed that snack consumption was associated with increased SBP and MAP, and not with DBP [28].…”
Section: Discussionmentioning
confidence: 98%